Design and Analysis of Different Components of an Air Handling Unit - Asif, Ifrah; Ghouri, Umaid; Hussain, Syed Taha; Siddiqui, Vissam; Ghazzal, Syed Ahmed; Naqvi, Syed Jari (TECCIENCIA, 2023)
AHU (air handling unit) is an imperative component of the HVAC (heating, ventilation and air conditioning) system as it is used to regulate conditioned air into the ducts of this system. AHU deals with the heat change between outdoor air and the air inside the working environment of any building. Designing of an AHU depends upon the specific requirements of temperatures inside the building and the components required achieving those targets. This paper provides a detailed aspect of all kinds of AHU and discusses the considerations taken while designing and choosing the components to be installed inside the AHU. Furthermore it mentions the required calculations necessary for the design of centrifugal blower unit and for the selected heat exchanger coil. Moreover, it contains the design of the components and a two dimensional drawing of the Air Handling Unit. The two dimensional drawing was obtained upon validations of our selected blower unit and heat exchanger coil.